INVESTIGATION ON POTENTIAL IONIC LIQUIDS FOR EXTRACTIVE DESULFURIZATION OF DIESEL - ABDULLAH, SYAMSUL BAHARI (2012)
The prospect of ionic liquids (ILs) as industrial solvent for desulfurization process may be illustrated from several explanations of the solute-solvent interaction point of view. For the aromatic organosulfur as a solute, the explanations of its miscibility in ILs are mostly described through n-electron density by means of n-n or CH-n interaction mechanism. The prediction using COSMO-RS which majorly rely on hydrogen bonding mechanism, showed inconsistent results against experimental data. The present study using Raman spectroscopy has led to the same conclusion where nelectron density becomes a vital viewpoint in the process of screening potential ILs for desulfurization. The use of a new complementary method which estimates the aromaticity index (AI) for cation and double bond equivalent (DBE) for anion selection showed good agreement between the literature and experimental results. The AI and DBE methods were later used to select the appropriate combination of cation and anion ofiLs for extractive desulfurization study. From the 407 potential ILs selected based on COSMO-RS database, 25 ILs as suggested from the complementary method were synthesized for further evaluation. Out of the 25, some which are commercially available were purchased for validation purposes. The synthesized ILs were characterized accordingly by 1 H NMR, 13C NMR, elemental analysis, and halide content including their water contents, densities and refractive indices. A single batch extraction at room temperature for extracting benzothiophene (BT) from model oil (n-C12) was well studied to determine the optimum extracting conditions of stirring speed and extraction time. The effect of three important process variables (mass ratio, BT concentration and temperature) were also investigated using Response Surface Methodology (RSM).